Cultural Exploration of Outer Baduy: Preserving Woven Fabrics Through Photographic Narratives - Nico Cheyrol Gainer; Pongky Adhi Purnama; Daniel Marlasputra Simbolon (Gorga : Jurnal Seni Rupa, 2025)
This work documents the preservation process of woven fabric by the Outer Baduy Community through a narrative photo story approach. The observation focuses on the family of Mr. Jamal in Kanekes Village. The weaving activity, passed down through generations by women, reflects obedience to tradition and cultural identity. This study aims to create photographic works that visually and informatively portray the preservation of Baduy Culture. Using a Practice-Based Research method, the author was directly involved in the creation and observation process. The result is a series of photographs that not only document but also deliver educational value about local cultural preservation. The research concludes that visual narrative is an effective medium to convey cultural messages to the wider audience. The urgency of this research lies in the increasing threat of cultural erosion caused by modernization, which can reduce the younger generation’s interest in continuing traditional weaving practices. Without proper documentation and dissemination, valuable knowledge and techniques risk disappearing over time. By employing narrative photography, this work not only preserves visual records of the weaving tradition but also provides a medium to raise awareness, inspire cultural pride, and encourage sustainable preservation efforts. Such initiatives are essential to ensure that the Baduy weaving heritage remains a living practice rather than a static artifact of the past.